A new species of Quwatanabius Smetana (Coleoptera, Staphylinidae, Staphylininae) from Guangxi, South China - Hu, Jia-Yao; Li, Li-Zhen; Zhao, Mei-Jun (Zootaxa, 2013)
A new species of Quwatanabius Smetana, Q. dayaoensis Hu, Li & Zhao sp. n. from Dayao Mountain, Guangxi Province, China, is described and illustrated. An identification key to species of Quwatanabius is provided.